Hubungan Pengetahuan dan Pola Asuh Ibu Dengan Tumbuh Kembang Bayi 3-12 Bulan - Musanna, Khadijatul; Lase, Eltin Murni; Laia, Endang Karnita Nevi; Silalahi , Farida Linawati; Hidayat, Anisa Nur; Nababan, Tiarnida (Journal of Pharmaceutical and Sciences, 2025)
Background: The World Health Organization (WHO) reports that 52.9 million infants worldwide experience developmental disorders, with 54% of these cases potentially exhibiting developmental abnormalities. In low- and middle-income countries, nearly 95% of individuals face developmental delays, while in the United States, behavioral or developmental issues affect 15-18% of children. Research Objectives: This study aims to analyze the influence of maternal attitudes and practices on the growth and development of infants aged 3-12 months in Tanjung Gusta Subdistrict, Klambir IV Region, specifically at Midwife Elly's Clinic. Methods: Employing a quantitative approach with a cross-sectional design, this study utilized non-probability sampling through quota sampling technique. Seventy-one participants were included as research subjects. Results: The findings at Midwife Elly's Independent Practice Clinic revealed a significant correlation between parental knowledge and child development in infants aged 3-12 months (p-value = 0.000; p < 0.05 based on chi-square test). Additionally, the study identified an association between maternal knowledge and emotional well-being with child development within this age range.